Cesium Fluoride and Copper‐Catalyzed One‐Pot Synthesis of Benzoxazoles via a Site‐Selective Amide C−N Bond Cleavage. Issue 17 (19th July 2019) - Luo, Zhongfeng; Wu, Hongxiang; Li, Yue; Chen, Yuwen; Nie, Jingyi; Lu, Siqi; Zhu, Yulin; Zeng, Zhuo
Abstract: We report herein a two‐step one‐pot strategy for the synthesis of benzoxazoles from amides by using cesium fluoride/copper as catalysts. This approach involves the in situ generation of acyl fluorides from the corresponding amides, and the acyl fluorides undergo transamidation and cyclization to give benzoxazoles in good yields. In this work, the amide C−N bonds are activated by CsF to form the acyl fluoride intermediates, which further react with o ‐bromoanilines to efficiently yield benzoxazoles. Notably, this methodology demonstrates a broad substrate scope, as primary/secondary benzamides are well tolerated, and this process might facilitate the development of one‐pot transformations of amides. Abstract :